The Role of Artificial Intelligence (AI) in Encouraging Research Learning to Sharpen 21st-Century Skills at Mts Negeri 6 Boyolali - Anggie Pramulyastuti; Syamsul Huda Rohmadi (Penerbit Hellow Pustaka, 2025)
The development of technology through the emergence of Artificial Intelligence (AI) has brought many conveniences, particularly in the fields of education and research. Along with the 21st-century demands known as the 4Cs (creative, critical, communicative, and collaborative), which are implemented through research-based learning in madrasahs, this raises the question of how AI plays a role in enhancing students’ 21st-century skills. This study aims to analyze the role of Artificial Intelligence (AI) in promoting research-based learning to develop 21st-century competencies at MTs Negeri 6 Boyolali. Research-based learning is important to train 21st-century skills, which include literacy, critical thinking, creativity, communication, and collaboration—commonly referred to as the 4Cs. Technological advancements, including the availability of Artificial Intelligence (AI), provide various tools that make many tasks easier, especially in research-based learning. This study employs a qualitative approach using interviews, observations, and documentation methods. The subjects of this study are students in the research class, while the informants are the teachers who serve as research class mentors. The results of this study indicate that Artificial Intelligence (AI) plays a significant role in promoting research-based learning to enhance 21st-century skills at MTs Negeri 6 Boyolali. The presence of AI provides convenience and stimulates 21st-century competencies, including literacy, critical thinking, creativity, communication, and collaboration. However, there are also several challenges encountered in the use of AI in the learning process.